2015
DOI: 10.1149/2.0431512jes
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption and Recovery in Capacitive Deionization Using Nanoporous Activated Carbon Electrodes

Abstract: Capacitive deionization (CDI) is an emerging desalination technology which utilizes porous electrodes to remove ions in water by electrosorption. Similar to electric capacitors, energy is stored and released during charging and discharging cycles, respectively. In this study, a nanoporous activated carbon coupled flow-through CDI device was used to evaluate energy consumption and recovery under various operational conditions by charging and discharging the cell at a constant current, respectively. Results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 36 publications
3
28
0
1
Order By: Relevance
“…In fact, only a handful of published studies on CDI even report thermodynamic efficiency values. [23,24] Further, there has been no overview of the current typical values of CDI thermodynamic efficiency or of methods by which it can be improved.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, only a handful of published studies on CDI even report thermodynamic efficiency values. [23,24] Further, there has been no overview of the current typical values of CDI thermodynamic efficiency or of methods by which it can be improved.…”
Section: Introductionmentioning
confidence: 99%
“…Capacitive deionization (CDI) with electric double layers is an electrochemical desalination technology in which porous carbon electrodes are polarized at a constant current or voltage to decrease the salinity of water (Anderson et al., 2010; E. Suss et al., 2015; Porada et al., 2013). When discharged under constant current, regeneration of CDI salt removal capacity can be coupled to energy recovery (Długołęcki and van der Wal, 2013; Han et al., 2015; Tan et al., 2018; Zhao et al., 2012). A typical cell architecture involves the flow of feed solution in the channel created by the separation of porous carbon electrodes, called flow-by or flow-between CDI (fb-CDI) (Bouhadana et al., 2010; E. Suss et al., 2012; Porada et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Kang et al [153] show that CC-CDI consumes approximately 30% less energy than CV-CDI for identical electronic charge storage or identical ion removal, without considering energy recovery. Similar differences in energy consumption between CC and CV modes without considering energy recovery were reported by Choi [36] and by Han et al [154]. A much higher advantage of CC over CV implied Ref.…”
Section: Introductionsupporting
confidence: 83%
“…Note that this choice does not need to be made for steady state operation of CDI with flowing electrodes, but is only necessary for cyclic processes. For carbon electrodes (which we consider from this point onward), in literature it is reported that CC operation leads to a lower energy consumption than CV operation [36,97,[153][154][155][156]. Kang et al [153] show that CC-CDI consumes approximately 30% less energy than CV-CDI for identical electronic charge storage or identical ion removal, without considering energy recovery.…”
Section: Introductionmentioning
confidence: 99%